ANALISIS LABOUR UTILITATION RATE TENAGA KERJA (Studi Kasus Proyek Bintaro Jaya Xchange Tahap II, Tangerang Selatan) - Galih Wulandari Subagyo (Universitas Trisakti, 2022)
Labor productivity is one of the many factors that can influence the success of a development project in the construction industry.The LUR (Labor Utilitation Rate) parameter of each worker is one method for measuring labor productivity. Several factors influenced worker productivity during the pandemic, including age, work experience, education level, wage suitability, family responsibilities, worker health, health impact, development of health protocols, worker relations, and management. The goal of this study was to determine the level of productivity (LUR) of each worker at the Bintaro Jaya Xchange Phase II Project during the Covid-19 pandemic, with the limitations of the research being data collection through observation with research time conducted Monday through Friday (Weekdays), Saturday through Sunday (Weekend) at 08.00 WIB to 16.00 WIB (for 7 working days). According to the findings of the study, Leso, Rahman, Didi, Basuki, Saluyu, and Caca had the highest LUR (Labor Utilitation Rate), at 86.61%. While the national average LUR (Labor Utilitization Rate) is 79.53%. As a result of the data obtained, it is possible to conclude that the level of work productivity at work during the Covid-19 pandemic was satisfactory, owing to a worker utility factor or LUR (Labor Utilization Rate) value of more than 50%